10 nm SiO2 TM Slot Mode in Laterally Mismatched Asymmetric Fin-Waveguides - Byers, James; Debnath, Kapil; Arimoto, Hideo; Husain, Muhammad K.; Sotto, Moïse; Hillier, Joseph; Kiang, Kian; Thomson, David J.; Reed, Graham T.; Charlton, Martin; Saito, Shinichi (Frontiers in Physics, 2021)
In this paper we demonstrate that by breaking the left/right symmetry in a bi-planar double-silicon on insulator (SOI) photonic crystal (PhC) fin-waveguide, we can couple the conventionally used transverse-electric (TE) polarized mode to the transverse-magnetic (TM) polarization slot-mode. Finite difference time domain (FDTD) simulations indicate that the TE mode couples to the robust TM mode inside the Brillouin zone. Broadband transmission data shows propagation identified with horizontal-slot TM mode within the TE bandgap for fully mismatched fabricated devices. This simultaneously demonstrates TE to TM mode conversion, and the narrowest Si photonics SiO2 slot-mode propagation reported in the literature (10 nm wide slot), which both have many potential telecommunication applications.